Clinical outcomes and adverse events of nontuberculous mycobacterial lung disease treated at an Italian tertiary referral center - Carli, Serena Maria; Mencarini, Paola; Licata, Maria Angela Vittoria; Musso, Maria; Cerva, Carlotta; Mastrobattista, Annelisa; Vittozzi, Pietro; Mosti, Silvia; Nisii, Carla; Mazzarelli, Antonio; Navarra, Assunta; De Carli, Gabriella; et al. (Scientific reports, 2025)
Treatment of NTM lung disease (NTM-LD) is based on combinations of antimycobacterial drugs. It lasts 12 months if respiratory samples become culture negative, while in refractory cases it can last up to 18–24 months. Therapeutic pathway is complicated by frequent adverse events (AEs). Sometimes, symptomatic therapy is not sufficient to control AEs, making necessary to suspend the drug involved or the entire treatment. This study aims to describe the frequency and type of AEs in patients with NTM-LD and to evaluate their impact on the outcomes of treatment. This is a retrospective observational study. We analysed clinical data, regimen composition, AEs and outcomes of NTM-LD patients followed between January 2016 and June 2023 at the National Institute for Infectious Diseases “L. Spallanzani” in Rome. Out of 131 patients, fifty-eight (44.3%) were men; median age was 66 years (IQR: 56–73). One hundred (76.3%) developed AEs. Total AEs were 229, of which 81 were serious adverse events (SAEs). Cure was obtained in 113 cases (86.3%), therapeutic failure occurred in 10 (7.6%), 6 patients died (4.6%), and 2 (1.5%) were lost-to-follow-up. Despite of AEs, most patients were able to complete treatment with appropriate management and monitoring. AEs affect patient quality of life and treatment adherence. Therefore, it is important to identify factors that can predict and prevent them. Clear and detailed information about drug side effects, with instructions to follow in case of AEs, active monitoring at every contact, flexibility and accessibility to healthcare professionals are key factors for therapy success.